Correlation between an In Vitro Invasion Assay and a Murine Model of Burkholderia cepacia Lung Infection - Cieri, Martin V. (American Society for Microbiology, 2002)
Our understanding of the virulence of Burkholderia cepacia complex lung infections in cystic fibrosis patients is incomplete. There is a great deal of variability in the clinical course, from simple colonization to severe and often fatal necrotizing pneumonia, termed cepacia syndrome. Multiple subspecies (called genomovars) have been identified, and these genomovars may hold the key to understanding the variable pathogenicity. Thirty-one B. cepacia complex isolates belonging to five of the seven genomovars were examined by using a gentamicin protection assay of invasion with A549 cells. The level of epithelial cell invasion by B. cepacia in the A549 model was relatively low compared with the data obtained for other pathogens and was often variable from assay to assay. Thus, a statistical approach was used to determine invasiveness. When this model was used, one of four genomovar I strains (25%), three of eight genomovar II strains (37.5%), seven of nine genomovar III strains (77.8%), one of four genomovar IV strains (25%), and none of the four genomovar V strains examined were defined as invasive. All other strains were categorized as either noninvasive or indeterminate. Invasive, noninvasive, and indeterminate isolates belonging to genomovars II and III were subsequently tested for splenic invasion with the mouse agar bead model. Correlation between the models for six strains was demonstrated. Our results indicate that a statistical model used to determine invasiveness in an in vitro invasion assay can be used to predict in vivo invasiveness.